The Great Stereopticon Revisited - G. Daniel Harden (Educational Considerations, 1999)
In 1948 Richard Weaver, a somewhat reclusive professor of literature at the University of Chicago, produced what came to be the widely acclaimed and quoted book, Ideas Have Consequences. The work received critical commentary at the time from both enthusiasts and detractors.